Mitochondrion at the Crossroad Between Nutrients and Epigenome - Taormina, Giusi; Russo, Antonio; Latteri, Mario A.; Mirisola, Mario G. (Frontiers in Endocrinology, 2019)
Epigenetic profile is the link between the regulation of nuclear gene expression and the environment. The most important factors capable of significantly affecting the cellular environment are the amount and quality of nutrients available. Mitochondria are both involved in the production of some of the molecules capable of directly affecting the epigenome and have a critical role in the conversion of nutrients into usable energy. Carbohydrate and fats are converted into ATP, acetyl-CoA, SAM, and NADH. These high-energy substrates are, in turn, capable of driving the epigenetic profile. We describe substances capable of affecting this mechanism. On the other hand, nutritional interventions capable of reducing calories or significantly impairing the normal Acetyl-CoA production or the SAM-SAH ratio also impact chromatin methylation and histone modification, suggesting a critical role of mitochondria on nutrient-dependent epigenetic profile.